The local charge carrier interaction with lattice defects in ZnCdTe and ZnHgTe solid solutions - Malyk, O.P. (Functional Materials, 2009)
The processes of the charge carrier scattering on the short-range potential caused by interaction with polar and nonpolar optical phonons, piezoelectric and acoustic phonons, static strain, neutral and ionized impurities in ZnₓCd₁₋ₓTe (0x1) and ZnₓHg₁₋ₓTe (x = 0.15) are considered. The temperature dependence of the charge carrier mobility in temperature range 50-360 K are calculated.